Strengthening Teachers' Capabilities in Learning and Writing Questions based on Higher Level Thinking Skills: Penguatan Kemampuan Guru dalam Pembelajaran dan Penyusunan Soal berbasis Keterampilan Berfikir Taraf Tinggi - Anas Arfandi; Akshari Tahir Lopa (Yayasan Ahmar Cendekia Indonesia, 2023)
The ability of students to apply higher order thinking skills is a challenge for teachers. These thinking skills are directed at the ability to solve problems. Students' is still difficult to connect the real situation they face. The community partnership program activities were carried out using lecture, discussion, question and answer, and practice. The steps taken are: (1) provide an understanding of learning and preparation of evaluation questions on learning outcomes; (2) provide counseling and evaluation of HOTS-based learning outcomes; (3) conducting HOTS-based question-making skills training; (4) conduct item analysis training. The results obtained show that the understanding of teachers at SMP Negeri 2 Tinambung has increased after being given training. Teachers have also been able to compile HOTS-based questions. Abstrak Kemampuan siswa dalam menerapkan keterampilan berpikir taraf tinggi menjadi tantangan tersendiri bagi guru. Keterampilan berfikir tersebut diarahkan pada kemampuan memecahkan masalah. Pemahaman siswa masih sulit menghubungkan dengan situasi nyata yang mereka hadapi. Kegiatan program kemitraan masyarakat (PKM) kali ini dilakukan dengan metode ceramah, diskusi, tanya jawab, dan latihan. Adapun tahapan yang dilakukan adalah: (1) memberikan pemahaman mengenai pembelajaran dan penyusunan soal evaluasi hasil belajar; (2) memberikan penyuluhan dan evaluasi hasil belajar berbasis HOTS; (3) melakukan pelatihan keterampilan membuat soal berbasis HOTS; (4) melakukan pelatihan analisis butir. Hasil yang diperoleh menunjukkan bahwa pemahaman guru SMP Negeri 2 Tinambung meningkat setelah diberi pelatihan. Guru juga telah mampu menyusun soal berbasis HOTS.